UTILIZATION OF MICROALGAE Scenedesmus vacuolatus AS A PHOSPHATE (PO43-) BIOREMEDIATOR IN DOMESTIC WASTEWATER - Fathoni, Ahmad Yusron; Nursyirwani, Nursyirwani; Effendi, Irwan; Ambarsari, Hanies (Asian Journal of Aquatic Sciences, 2020)
This research was conducted in October 2019 to determine the effect of differences in the addition of KH2PO4 concentrations and the concentration of microalgae Scendesmus vacuolatus with experiment method. The results showed significant effect was found on differences in microalgae concentration and KH2PO4 concentration. KH2PO4 with the concentration of 8 ppm is the most influential on decreasing phosphate levels than KH2PO4 with 5 ppm. The highest samples in phosphate reduction were A2, B2 and C2 with different algal formulations and 8 ppm KH2PO4 concentration. Two-way ANOVA test showed sig. 0.000, Which was mean that there were significant effect to decrease levels of phosphate based on concentration. Post hoc DMRT which has a significantly different dominance value of KH2PO4 concentration results that A1, B1, C1 with A2, B2, C2 have significant differences in the decrease in phosphate levels due to differences in KH2PO4 levels.